What do families value most about the care home where their older adult relatives live? - Eduardo Alberto Leché-Martín; María Isabel Saz-Gil; Ana Isabel Gil-Lacruz; María José Sierra-Berdejo; Marta Gil-Lacruz (Frontiers Media S.A., 2024)
IntroductionThe 2030 Agenda and the principles of Corporate Social Responsibility (CSR) define companies and public authorities as agents for social change sharing objectives such as promotion of health, personal development and social engagement, among others. Care homes for the older adult are an example of organizations that should be particularly aware of these priorities. Since they work with vulnerable groups, collaboration with the families is essential in ensuring residents' wellbeing.MethodsThe objective of this study is to analyse the factors that condition the satisfaction of relatives of residents in a care home for the older adult located in a rural environment in the province of Huesca (Spain).Results and discussionThe 51 relatives interviewed rated the following points very positively: location and accessibility, food service, medical resources, communication with the staff and management team. A high percentage, however, did not know about the channels for volunteer work and institutional involvement. Some psychosocial indicators related to families' interaction and communication with the staff and their potential involvement in the dynamics of the institution have considerable weight in how they explain their satisfaction. These results may lead to new lines of research and intervention that contribute to improving the quality of this type of resources and their commitment to the Sustainable Development Goals (SDGs) and social responsibility.